AB0726 Combination Therapy with Bosentan and Sildenafil Improves Nailfold Videocapillaroscopy in Systemic Sclerosis (SSC). (9th June 2015) - Bellando Randone, S.; Lepri, G.; Bruni, C.; Blagojevic, J.; Radicati, A.; Guidi, F.; Cometi, L.; Matucci-Cerinic, M.; Guiducci, S.
Abstract : Background: Raynaud's Phenomenon (RP) is often the first sign of Systemic Sclerosis (SSc) vasculopathy and several drugs (calcium channel blockers, prostanoids, Endothelin 1 receptor antagonists, phosphodiesterase-5 inhibitors are commonly used to reduce frequency and severity of RP attacks. Objectives: The aim of our study was to evaluate retrospectively the efficacy of different vasoactive therapeutic regimens, particularly of Bosentan and Sildenafil, on the quality of life and apillaroscopic patterns in SSc patients. Methods: 123 SSc patients (mean age sd: 57.69±14.07 years) were retrospectively evaluated. Patients were arbitrarily divided into 2 groups according to ACR/EULAR classification score: group 1 with score ≤10, group 2 with score >10. Each group was then divided into 3 subgroups according to different vasoactive treatment: Bosentan, Sildenafil, and Bosentan plus Sildenafil. Nailfold videocapillaroscopy (NVC) was performed at baseline and after 3 and 6 months as well as SHAQ (Scleroderma Health Assessment Questionnaire) and RCS (Raynaud Condition Score). Results: 29 patients were on Bosentan (12 patients of group 1; 17 of group 2), 63 patients on Sildenafil (35 patients of group 1; 28 of group 2) and 31 patients on combination of Bosentan plus Sildenafil (14 patients of group 1; 17 of group 2). Patients on Bosentan: The capillaroscopic pattern changed significantly, both after 3 months (p=0, 00439 group 1, p=0, 00076 group 2) and after 6 months (p=0, 00439 group 1, p=0, 00035 group 2) of treatment, if compared to baseline, in both groups. In group 1, both the "active" that the "late" patterns were reduced while the "aspecific" pattern increased. In group 2, there was a reduction of percentage of "late" pattern. In group 1, SHAQ and RCS did not change while in group 2 SHAQ worsened significantly (p<0.005) and RCS improved (p=0, 00014). Patients on Sildenafil: After 3 months of treatment, in both groups the NVC patterns changed significantly (p=0.042 group 1, p=0, 00089 group 2). In particular, in group 1 the "late" and "early" patterns increased while the "asepcific" pattern decreased. In group 2, a significant change of NVC pattern was observed also after six months of treatment (p=0, 00089), in particular the "late" pattern increased while the "active" pattern reduced. After 6 months SHAQ significantly reduced both in group 1 (p=0, 00027), that in group 2 (p=0, 0043). RCS improved in both groups (p=0, 0042 group 1, p=0, 0016 group 2). Patients on combination therapy (Bosentan+Sildenafil): Only in group 1, combination therapy induced significant changes on NVC patterns both after three months (p=0, 00256) and after 6 months of treatment (p=0, 000349). In particular, a progressive reduction of the "late" "active" patterns was observed, while the "early" pattern increased. In group 2 no pattern modification was observed. In both groups, after 6 months SHAQ was significantly reduced (p<0, 05 group 1, p=0, 00049 group 2), and RCS was reduced (in group 1, p=0, 00024; group 2, p=0, 0021). Conclusions: SSc patients treated with Bosentan/Sildenafil combination had a significant improvement of the microvascular involvement when compared to Bosentan and Sildenafil alone. The combination achieved a modification of the NVC pattern thus fostering microvascular de-remodelling. Disclosure of Interest: None declared